Building workforce well‐being capability: The findings of a wellness self‐care programme. (9th February 2021) - Wilson, Valerie; Donsante, Jacqueline; Pai, Padmini; Franklin, Alison; Bowden, Alera; Almeida, Shamika
Abstract: Aim: To implement and evaluate a co‐designed staff well‐being programme. Background: Working in health care can be physically and psychologically demanding. The job demands–resources model indicates job resources moderate the impact of job demands on staff well‐being. Well‐being initiatives introduced by organisations improve staff commitment, and reduce absences and incidents. Methods: A qualitative descriptive design was applied. In 2019, within an Australian local health district, 232 health care professionals across eight hospitals and two community settings attended a six‐week well‐being programme, which included a variety of self‐care strategies, for example mindfulness. Nine 1‐hr focus groups were completed 2–4 weeks post‐programme. Data were analysed using thematic analysis to explore participants' thoughts and experiences. Results: Participants experienced joy from workshops and guilt for leaving peers with their workload. Participants developed strong interpersonal relationships with workshop attendees within a 'safe well‐being space'. Broader impacts expressed by participants were; learnt coping mechanisms and proactive self‐care practices and can be easily embedded into daily routines. Participants shared their 'toolkit' with colleagues, family and friends, positively impacting the well‐being of people around them. Conclusion: Participants encouraged by their new well‐being 'toolkit' engaged with colleagues, better managed stressors and shared learnings. Implications for Nursing Management: Building well‐being capability within a health organisation requires nursing management to make staff well‐being a strategic priority, use a co‐design approach and embed coping mechanisms at the grassroots levels.